2018
DOI: 10.3892/ol.2018.7948
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced dynamic and diffusion-weighted magnetic resonance imaging at 3.0�T to assess early-stage�nasopharyngeal carcinoma

Abstract: Abstract. The present study aimed to assess early-stage nasopharyngeal carcinoma (NPC) with dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and diffusion-weighted imaging (DWI) at 3.0 T. A total of 44 patients newly diagnosed with NPC were included in the present study. All patients underwent MR examination at 3.0 T using DCE-MRI and DWI. The volume transfer constant (K trans ), flux rate constant between extravascular extracellular space and plasma (K ep ), the volume of extravascular extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…In addition,K ep was the highest in HER-2-enriched BC and the lowest in luminal A. This finding was consistent with the results of previous studies that indicated that more aggressive tumors have a higher K ep value (21).…”
Section: Discussionsupporting
confidence: 92%
“…In addition,K ep was the highest in HER-2-enriched BC and the lowest in luminal A. This finding was consistent with the results of previous studies that indicated that more aggressive tumors have a higher K ep value (21).…”
Section: Discussionsupporting
confidence: 92%
“…Despite this, our findings are in line with several prior studies supporting the hypothesis that proliferative tumours with higher cellularity are likely to have higher vascular permeability. Ni, Liu [13] reported in their study for NPC with DCE-MRI and DW-MRI scans using a 3T MR scanner, that a negative correlation was found with K trans and ADC in their cohort. Our results support their findings regarding K trans and ADC correlation.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have shown that baseline tumour plasma perfusion is predictive in chemotherapy treatment response for patients with head and neck cancers [10] , [11] . Studies have indicated that tumour permeability is associated with the diffusivity and clinical stage of NPC [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, DCE-MRI has emerged as a valuable technique for investigating the properties of tissue microvasculature. Using a 3.0 T MRI scanner, Ni and Liu[ 18 ] have reported negative correlations between ADC and DCE-MRI parameters ( K trans , k ep, or v e ) in 44 patients with NPC. In keeping with their findings, we identified a significant negative association between ADC and K trans or v e .…”
Section: R Esultsmentioning
confidence: 99%